2017
DOI: 10.1021/acs.organomet.7b00654
|View full text |Cite
|
Sign up to set email alerts
|

T-Shaped Gold→Stiborane Complexes as Carbophilic Catalysts: Influence of the Peripheral Substituents

Abstract: As part of our efforts toward the discovery of new late transition metal catalysts, we synthesized [(o-(Ph 2 P)C 6 H 4 ) 2 (o-C 6 Cl 4 O 2 )SbPh)Au] + (3 + ) and [(o-(iPr 2 P)-C 6 H 4 ) 2 (o-C 6 Cl 4 O 2 )SbPh)Au] + (4 + ), two cationic bis-(phosphino)gold stiborane complexes, which were isolated as their hexafluorophosphate salts and fully characterized.Structural and computational studies indicate that the cores of these two complexes are almost structurally and electronically identical. Despite these simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 78 publications
1
20
0
Order By: Relevance
“…Its XRD structure ( Figure 6) confirmed that the molecule arises from the insertion of the Ge atom of 1 into the AuÀCl bond of the gold precursor, resulting in ac omplex containing aP GeP pincer chloridogermyl ligand attached in aT -shape mode to ag old(I) atom (the originalT HT ligand was displaced from the gold atom). Comparing the AuÀEd istances in ZEZ-pincer T-shaped gold(I) complexes (Figure7), the Au1ÀGe1 distance of 5,2 .7639 (7) , is similar to the AuÀSb distances of the CSbC complexes of Gabbaï et al,2 .7694(8)a nd 2.7486 (7) , [23] much shorter than the AuÀSb distances of the PSbP complexes of Gabbaï et al, which are in the range 2.995-2.932 , [24] and longert han the AuÀBd istance of the PBP complex of Inagaki et al, [25] 2.521 (2) ,t he AuÀNd istances of the CNC complexes of Bezuidenhout et al,2 .325 (2) for Ar = 2,6-bis(isopropyl)phenyl (Dipp) and (2),P t1ÀP2 2.360 (2),P t1ÀGe1 2.3140 (8), Pt1ÀCl2 2.364(2), Ge1ÀCl1 2.209(2), Ge1ÀN1 1.864 (7), Ge1ÀN2 1.852 (7);N1-Ge1-N2 101.4 (3), N1-Ge1-Pt1 122.3 (2), N2-Ge1-Pt11 17.9(2), N1-Ge1-Cl1 101. 3(2),N 2-Ge1-Cl1 100.0(2), Cl1-Ge1-Pt1 110.72 (6), Ge1-Pt1-Cl2 169.10 (6), P1-Pt1-P2 168.84 (7), P1-Pt1-Ge1 90.79 (5), P2-Pt1-Ge1 88.61 (5),P1-Pt1-Cl2 91.70 (7),P2-Pt1-Cl2 90.97(7).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Its XRD structure ( Figure 6) confirmed that the molecule arises from the insertion of the Ge atom of 1 into the AuÀCl bond of the gold precursor, resulting in ac omplex containing aP GeP pincer chloridogermyl ligand attached in aT -shape mode to ag old(I) atom (the originalT HT ligand was displaced from the gold atom). Comparing the AuÀEd istances in ZEZ-pincer T-shaped gold(I) complexes (Figure7), the Au1ÀGe1 distance of 5,2 .7639 (7) , is similar to the AuÀSb distances of the CSbC complexes of Gabbaï et al,2 .7694(8)a nd 2.7486 (7) , [23] much shorter than the AuÀSb distances of the PSbP complexes of Gabbaï et al, which are in the range 2.995-2.932 , [24] and longert han the AuÀBd istance of the PBP complex of Inagaki et al, [25] 2.521 (2) ,t he AuÀNd istances of the CNC complexes of Bezuidenhout et al,2 .325 (2) for Ar = 2,6-bis(isopropyl)phenyl (Dipp) and (2),P t1ÀP2 2.360 (2),P t1ÀGe1 2.3140 (8), Pt1ÀCl2 2.364(2), Ge1ÀCl1 2.209(2), Ge1ÀN1 1.864 (7), Ge1ÀN2 1.852 (7);N1-Ge1-N2 101.4 (3), N1-Ge1-Pt1 122.3 (2), N2-Ge1-Pt11 17.9(2), N1-Ge1-Cl1 101. 3(2),N 2-Ge1-Cl1 100.0(2), Cl1-Ge1-Pt1 110.72 (6), Ge1-Pt1-Cl2 169.10 (6), P1-Pt1-P2 168.84 (7), P1-Pt1-Ge1 90.79 (5), P2-Pt1-Ge1 88.61 (5),P1-Pt1-Cl2 91.70 (7),P2-Pt1-Cl2 90.97(7).…”
Section: Resultssupporting
confidence: 59%
“…The AuÀGe distances of "normal" (not T-shaped) mononuclear complexes containing germyl ligands are also shorter than that of complex 5,n amely,i nt he range of 2.362-2.423 . [28] It should be noted that T-shaped pincer gold(I) complexes are very rare, the only examples currentlyk nown being those depicted in Figure 7 [23][24][25][26][27] (most tricoordinate gold(I) complexes are trigonal planar [29] ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1i,j] Examples that illustrate the tunability of these ligand systems include double-decker complexes of type I where variation of the Group 13 element allows for the precise control of the Ni-E interaction [4] as well as complexes of type II where the redox state of the antimony center can be used to adjust the strength of the Au-Sb interaction ( Figure 1). [5] Based on the principle that cationic main group compounds are more Lewis acidic than their neutral counterparts, [6] we have been interested in an approach whereby anion abstraction serves to enhance the s-accepting properties of the Z-type ligand. [7] We demon-strated this idea in the case of complex III which, upon conversion into IV by fluoride anion abstraction, became catalytically active as ar esult of as tronger Pt!Sb interaction.…”
mentioning
confidence: 99%
“…We were also eager to test whether [4][NTf 2 ] 2 could be generated in situ, starting from [2a] [Cl].W efound that when generated in this way, [4][NTf 2 ] 2 showed acatalytic activity in the hydroamination of styrene that is almost identical to that observed when [3][NTf 2 ] 2 is used as ap recatalyst (entries [5][6][7][8]. This reaction is not activated by complex [3] 2+ or AgNTf 2 alone.When5mol %HNTf 2 was employed as acatalyst, only 16 %o fh ydroamination product was formed, and formation of polystyrene was observed.…”
mentioning
confidence: 99%